Influenza A virus associated with non-specific interstitial pneumonitis: First case report. Issue 4 (2nd October 2017) - Agabawi, Salem; Algamdi, Mohmmed; Blouw, Marcus; Qing, Gefei
ABSTRACT: A 77-year-old male presented with progressive shortness of breath (SOB) over three weeks. Initial chest x-ray (CXR) and computed tomography (CT) scan of the chest showed bilateral extensive airspace opacities and dense perihilar consolidation. Over the subsequent 48 hours, the patient suffered hypoxemic respiratory failure requiring transfer to the intensive care unit (ICU) for mechanical ventilation (MV) support. Bronchoscopy and Broncho-alveolar lavage (BAL) was done on the third day of admission and samples were negative for bacterial and fungal culture but confirmed the presence of influenza A virus using rRT-PCR method. Oseltamivir was started and continued for 10 days. Due to lack of improvement of hypoxemia and worsening air space opacities on CXR, open lung biopsy (OLB) was performed and demonstrated histopathology consistent with cellular non-specific interstitial pneumonitis (NSIP). Prednisone was started for NSIP. The patient was successfully liberated from MV and was eventually discharged home breathing on room air. RÉSUMÉ: Un homme de 77 ans a présenté un essoufflement progressif pendant trois semaines. Initialement, une radiographie et une tomodensitométrie du thorax ont révélé des opacités alvéolaires bilatérales généralisées et une consolidation péri-hilaire. Au cours des 48 heures suivantes, le patient a souffert d'insuffisance respiratoire hypoxémique, ce qui a nécessité son transfert à l'unité des soins intensifs pour y être mis sous ventilation mécanique. Une bronchoscopie et un lavage broncho-alvéolaire ont été effectués le troisième jour suivant son admission et des échantillons prélevés pour une culture bactérienne et fongique se sont révélés négatifs. Un traitement par oseltamivir a été débuté et s'est poursuivi pendant 10 jours. En raison de l'absence d'amélioration et d'une détérioration des opacités alvéolaires sur une radiographie du thorax, une biopsie à poumon ouvert a été réalisée et a démontré une histopathologie compatible avec une pneumonie interstitielle non spécifique. Un traitement par prednison a été débuté. Le patient a été sevré de la ventilation mécanique et respirait l'air ambiant lorsqu'il a finalement reçu son congé.